NiO-TiC composite materials: A study on structural integrity, dielectric behavior, and electrical conductivity - Macit, Cevher Kursat; Cetiner, Rumeysa; Horlu, Merve; Aydin, Derya; Biryan, Fatih; Koran, Kenan; Tanyeri, Burak (Elsevier, 2025)
In this study, titanium carbide (TiC) nanoparticles were incorporated into nickel oxide (NiO) semiconductors using the sol-gel method to enhance dielectric and electrical properties. Characterization techniques such as FTIR, XRD, FE-SEM, EDX, and Raman spectroscopy confirmed the structural integrity and successful dispersion of TiC in the NiO matrix. XRD showed distinct peaks for both NiO and TiC, while FE-SEM and EDX confirmed homogeneous TiC distribution. Impedance spectroscopy revealed that the dielectric constants (epsilon ' and epsilon '') and AC conductivity (sigma ac) significantly increased with TiC content. For 10 % TiC-doped NiO, epsilon ' and epsilon '' reached 49.596 and 256.242, respectively, while sigma ac improved to 1.250 x 10(-7) S/cm. I-V measurements showed enhanced current flow with increased TiC doping. Activation energy decreased from 0.038 eV to 0.023 eV, indicating improved charge transport. These results demonstrate that NiO-TiC nanocomposites are promising for electronic applications such as capacitors and solar cells.
Keywords: Nanomaterial; Sol-gel; Semiconductor; Nickel oxide; Titanium carbide; Conductivity